2016
DOI: 10.1590/1806-9282.62.04.324
|View full text |Cite
|
Sign up to set email alerts
|

Profile of pediatric eye trauma at Hospital de Base do Distrito Federal (HBDF), Brasília, Brazil

Abstract: Objective: To describe the epidemiological profile of ocular trauma in children at the HBDF emergency department. Method: Descriptive, cross-sectional study. We evaluated 103 cases of ocular trauma in children less than 15 years between July 2012 and January 2013. The factors evaluated through semi-structured questionnaire available online were: age, gender, adult supervision, mechanism, type of trauma, time and place, site and nature of injury, visual acuity, need for hospitalization and/or surgery, type of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 20 publications
2
10
0
Order By: Relevance
“…A low education level, lack of safety awareness and lack of protective eyewear may lead to the occurrence of eye injury. Additionally, we found that male children were more likely to be injured than female children, consistent with data from other studies [16,22,23].…”
Section: Discussionsupporting
confidence: 92%
“…A low education level, lack of safety awareness and lack of protective eyewear may lead to the occurrence of eye injury. Additionally, we found that male children were more likely to be injured than female children, consistent with data from other studies [16,22,23].…”
Section: Discussionsupporting
confidence: 92%
“…Most of the researchers have only broadly covered all the eye injuries in children [13][14][15][16][17][18][19]. Besides, several of the studies are concerned with small case series and are retrospective in nature [13][14][15][16][17][18][19]. Another key feature is that only a limited number of works have employed cross-sectional design [12].…”
Section: Discussionmentioning
confidence: 99%
“…Open globe injuries required intervention and were prevalent in 7-15 ears age group. 19 Movahedinnejad T et al have studied the incidence and cases of ocular trauma presenting to a hospital in Iran. The study was dominated by male sample size comprising 86% of cases.…”
Section: Discussionmentioning
confidence: 99%